Heat transfer study on convective–radiative semi-spherical fins with temperature-dependent properties and heat generation using efficient computational methods. (5th October 2015) - Atouei, S.A.; Hosseinzadeh, Kh.; Hatami, M.; Ghasemi, Seiyed E.; Sahebi, S.A.R.; Ganji, D.D.
Abstract: In this study, heat transfer and temperature distribution equations for semi-spherical convective–radiative porous fins are presented. Temperature-dependent heat generation, convection and radiation effects are considered and after deriving the governing equation, Least Square Method (LSM), Collocation Method (CM) and fourth order Runge-Kutta method (NUM) are applied for predicting the temperature distribution in the described fins. Results reveal that LSM has excellent agreement with numerical method, so can be suitable analytical method for solving the problem. Also, the effect of some physical parameters which are appeared in the mathematical formulation on fin surface temperature is investigated to show the effect of radiation and heat generation in a solid fin temperature. Highlights: Thermal analysis of a semi-spherical fin is investigated. Collocation and Least Square Methods are applied on the problem. Convection, radiation and heat generation is considered. Physical results are compared to numerical outcomes.